More than Bullshit: Trash Talk and Other Psychological Tests of Sporting Excellence. Issue 1 (2nd January 2020) - Johnson, Christopher; Taylor, Jason
ABSTRACT: Sporting excellence is a function of physical, cognitive and psychological capacities: its standard requires demonstration of superlative physical and strategic skills and the performance of these skills under pressure. However, despite the widespread acceptance of this idea there has been little exploration of what counts as a legitimate test of the psychological dimension. What work has been done has tended to focus on the practice of trash talking and whether the pressure that trash talking exerts is conducive to sporting objectives. However, not only do we believe that the philosophical work on trash talking is misguided, but also its conclusions have not been used to elucidate the legitimacy of other psychological pressures that occur in sport. In this paper we address this first lacuna by providing a more nuanced exploration of trash talking than exists in the philosophical literature, with the aim of addressing the second lacuna by suggesting a framework by which to evaluate other forms of psychological pressure that arise in sport. Briefly, our claim is that not all forms of trash talking that derail an opponent degrade, and that recipients of trash talking have both epistemic and social responsibilities in how they respond to trash talking. Moreover, these epistemic and social responsibilities can be extrapolated to evaluate the legitimacy of other forms of psychological pressure in sport, with forms that turn out to preclude broader social ends being morally illegitimate, and forms that do not preclude social ends yet facilitate meaningful challenges being legitimate tests of sporting excellence.